The ubc-2 gene of Caenorhabditis elegans encodes a ubiquitin-conjugating enzyme involved in selective protein degradation. - Zhen, M (1993)
The ubiquitin-protein conjugation system is involved in a variety of eukaryotic cell functions, including the degradation of abnormal and short-lived proteins, chromatin structure, cell cycle progression, and DNA repair. The ubiquitination of target proteins is catalyzed by a ubiquitin-activating enzyme (E1) and ubiquitin-conjugating enzymes (E2s) and in some cases also requires auxiliary substrate recognition proteins (E3s). Multiple E2s have been found, and these likely possess specificity for different classes of target proteins. Here we report the cloning and characterization of a gene (ubc-2) encoding a ubiquitin-conjugating enzyme which is involved in the selective degradation of abnormal and short-lived proteins in the nematode Caenorhabditis elegans. The nematode ubc-2 gene encodes a 16.7-kDa protein with striking amino acid sequence similarity to Saccharomyces cerevisiae UBC4 and UBC5 and Drosophila UbcD1. When driven by the UBC4 promoter, ubc-2 can functionally substitute for UBC4 in yeast cells; it rescues the slow-growth phenotype of ubc4 ubc5 mutants at normal temperature and restores their ability to grow at elevated temperatures. Western blots (immunoblots) of ubc4 ubc5 yeast cells transformed with ubc-2 reveal a protein of the expected size, which cross-reacts with anti-Drosophila UbcD1 antibody. C. elegans ubc-2 is constitutively expressed at all life cycle stages and, unlike yeast UBC4 and UBC5, is not induced by heat shock. Both trans and cis splicing are involved in the maturation of the ubc-2 transcript. These data suggest that yeast UBC4 and UBC5, Drosophila UbcD1, and C. elegans ubc-2 define a highly conserved gene family which plays fundamental roles in all eukaryotic cells.